Sistem Perakaran Bidara Laut (Strychnos lucida R. Br.) untuk Pengendalian Tanah Longsor - Ogi Setiawan; Budi Hadi Narendra (Jurnal Penelitian Kehutanan Wallacea, 2012)
One of potential Non Timber Forest Products (NTFPs) in West Nusa Tenggara and Bali is Strychnos lucida R.Br. which is used for medicinal purposes. The species is also potential to use in land rehabilitation of dry land where it offers an additional benefit of landslide control. Part of the plant which has important role in landslide control is root system. Therefore this study aimed to investigate the Strychnos lucida root system in landslide control. The study was held in Bali Barat National Park. Root characteristics observed in the study were the penetration position in the soil, root architecture, and Index of Roots Anchoring (IRA) and Index of Roots Binding (IRB). The result showed that Strychnos lucida root was able to penetrate into deep soil layer and had R-tipe root architecture which can increase shear resistance of soil. Value of IRA and IRB indicated the species had a more vertical roots in every growth stage and a high enough horizontal roots. Based on its root characteristics, Strychnos lucida was able to decrease landslide risk, especially shallow and surface landslide.